Seafood Innovation Processing Octopus into Flour and Proximate Composition Analysis as Highly Nutritious Food - Ayu Shinka Permata Sari; Bhakti Karyadi; Euis Nursa'adah; Nurhamidah; Rendy Wikrama Wardana; Indarini Dwi Pursitasari (Faculty of Tarbiyah and Teacher Training UIN Jurai Siwo, Lampung, 2026)
Kaur Regency has abundant marine resources, particularly Octopus vulgaris. According to data from the local Fisheries Service, octopus production in 2023 reached 349,310 kg. However, utilization remains limited to dried products. An alternative innovation is processing octopus into flour, which offers high nutritional value, longer shelf life, and broader applications as a raw material for various food products. This study aimed to produce octopus flour and analyze its proximate composition. Fresh octopus samples were selected, cleaned, boiled, sliced, and sun-dried until completely dehydrated. The dried material was then ground into powder and stored in airtight containers. Proximate and mineral analyses were conducted at the Biology Laboratory, University of Bengkulu, following SNI 01-2715-1996 standards. The macronutrient analysis showed that fat content was 8.19%, meeting SNI Class II standards (<10%). Protein content reached 32.41%, while carbohydrate content was 7.08%. For micronutrients, calcium content was 0.15%, meeting SNI Class I standards (>0.1%), magnesium content was 0.87%, and iron content was 5,412 ppm. Additional nutritional analysis indicated moisture content of 1.96%, fiber content of 0.73%, and ash content of 4.2%, all complying with SNI Class I criteria. In conclusion, octopus flour produced from local resources meets SNI Class I and II standards for macronutrients, micronutrients, and other nutritional parameters, demonstrating its potential as a nutritious and durable alternative food ingredient.